Implementasi Sistem Irigasi Smart Garden IoT pada Perkebunan Stroberi - Agnesia, Anisa; Kustidarsyah, Fajar; Andik Setiawan, I Made; Muharani, Laily (Politeknik Manufaktur Negeri Bangka Belitung, 2024)
In this research, the Smart Garden IoT system is implemented to enhance the efficiency of strawberry plant management, utilizing Ds18B20 temperature sensor, soil moisture sensor, water pH sensor, and a Flowmeter. Real-time data will be transmitted to the Blynk software for analysis. The research methodology involves the installation of sensors and the use of an ESP32 microcontroller in the strawberry cultivation area. The objectives of the study include improving monitoring and control, as well as supporting timely and efficient irrigation and fertilization of strawberry plants. This smart garden system operates according to predefined time settings and is also adjusted based on soil moisture sensor readings. The watering schedule is set for morning, afternoon, and evening. However, if the soil moisture remains around 80-90%, watering will be withheld. The research conclusion supports the concept of Smart Garden as an innovative solution to enhance efficiency in plant care through IoT technology